Effect of Ingestion Training Guided by Volume-viscosity Swallow Test on Post-Stroke Dysphagia - DENG Li; HE Yingzi; JIN Yanping; LU Yan (康复学报)
ObjectiveTo observe the effect of ingestion training guided by volume-viscosity swallow test (V-VST) on swallowing functions and quality of life of patients with dysphagia after stroke.MethodsA total of 150 patients with dysphagia after stroke who were treated in the Shanghai Sixth People's Hospital Affiliated to Shanghai Jiao Tong University from January 2019 to December 2020, were recruited and randomly divided into control group and observation group, with 75 cases in each group. The control group received traditional rehabilitation training, such as conventional therapy, cold stimulation training, mouthwash and so on, 15 minutes a time, twice a day, six days a week, lasting for eight weeks. The observation group received ingestion training guided by the V-VST in addition to the traditional rehabilitation training methods of the control group, 10 minutes a time, three times a day, six days a week, lasting for eight weeks. Before and after treatment, video fluoroscopy swallowing study (VFSS) was used to evaluate the swallowing functions; surface electromyography analysis system was used to detect surface electromyography (sEMG) and swallowing duration; upper arm and calf circumferences were measured and nutritional risk screening 2002 (NRS 2002) was used to evaluate the nutritional status of patients; the swallowing-quality of life (SWAL-QOL) scale was used to evaluate the quality of life; Rosenbek aspiration classification standard was used to evaluate the degree of aspiration.Results1) VFSS score: compared with those before treatment, the swallowing function scores in the pharyngeal and oral stages after treatment significantly increased in both groups (P<0.05). Compared with the control group, the swallowing function scores of the observation group in the pharyngeal and oral stages were significantly higher after treatment (P<0.05). 2) Swallowing duration and maximum amplitude of laryngeal muscle by sEMG: compared with those before treatment, the swallowing duration of laryngeal muscle measured by sEMG was significantly shortened and the maximum amplitude significantly increased in both groups (P<0.05). Compared with the control group, swallowing duration of laryngeal muscle by sEMG of the observation group was significantly shorter and the maximum amplitude was significantly higher after treatment (P<0.05). 3) Hyoid laryngeal complex mobility: compared with those before treatment, the distances of hyoid bone forward displacement and upward displacement of both groups significantly increased after treatment (P<0.05). Compared with the control group, the distances of the hyoid bone forward displacement and upward displacement of the observation group was significantly higher after treatment (P<0.05). 4) Nutritional status: compared with those before treatment, the upper arm and calf circumferences of both groups increased significantly after treatment, and the NRS 2002 score decreased significantly (P<0.05). Compared with the control group, the upper arm and calf circumferences of the observation group were significantly greater after treatment, and the NRS 2002 score was significantly lower (P<0.05). 5) Quality of life: compared with those before treatment, the SWAL-QOL scores of both groups increased significantly after treatment (P<0.05). Compared with the control group, the SWAL-QOL score of the observation group was significantly higher after treatment (P<0.05). 6) Degree of aspiration: compared with the control group, the degree of aspiration of the observation group was lower after treatment (P<0.05).ConclusionIngestion training guided by V-VST can improve the swallowing function of patients with dysphagia after stroke, reduce the degree of aspiration, and improve the nutritional status and quality of life.